Cardiovascular disease risk in a semirural community in Malaysia - Chia, Yook Chin; Srinivas, P. (SAGE Publications, 2009)
Background and aim: It has been argued that cardiovascular disease (CVD) is not very prevalent in developing countries, particularly in a rural community. This study examined the prevalence of CVD risk of a semirural community in Malaysia through an epidemiological survey. Methods: Subjects were invited to a free health screening service carried out over a period of 6 weeks. Then, a follow-up study of the initial nonresponders was done in the villages that showed a poorer response. The survey was conducted using a standardized questionnaire. Hypertension was defined as blood pressure ≥140/90 mm Hg. The Framingham Coronary Disease Risk Prediction Score (FRS) was used as a measure of CVD risk. Results: A total of 1417 subjects participated in this survey. The response rate was 56%. A follow-up survey of the nonresponders did not show any differences from the initial responders in any systematic way. The prevalence of CVD risk factors was high in both men and women. The mean (±SD) FRS was 9.4 (±2.5) and 11.3 (±4.1) for men and women, respectively. The mean predicted coronary heart disease (CHD) risk was high at 20% to 25% for men and medium at 11% to 13% for women. Overall, 55.8% of the men had >20% risk of having a CHD event in the next 10 years whereas women’s risk was lower, with 15.1% having a risk of ≥20%. Conclusion: The prevalence of CVD risk even in a semirural community of a developing country is high. Every effort should be made to lower these risk factors.